2014
DOI: 10.1002/gj.2577
|View full text |Cite
|
Sign up to set email alerts
|

40Ar/39Ar dating, fluid inclusions and S–Pb isotope systematics of the Shabaosi gold deposit, Heilongjiang Province, China

Abstract: The Shabaosi deposit is the only large lode gold deposit in the northern Great Xing'an Range. The gold ore bodies are hosted by sandstone and siltstone of the Middle Jurassic Ershi'erzhan Formation, and are controlled by three N–S‐trending altered fracture zones. The gold ore bodies are composed of auriferous quartz veinlets and altered rocks. Fluid inclusion studies indicate that the ore‐forming fluids belong to a H2O–NaCl–CO2–CH4 system, with salinities between 0.83 and 8.28 wt% NaCl eq., and homogenization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The sulphide ores have δ 34 S values of −23.2‰ to −0.5‰ (average −10.6‰) showing a wide negative range. This feature is similar as some sediment‐hosted orogenic gold deposits distributed in the northern margin of the NCC, in the eastern part of the Yilgarn Craton or in New Zealand (Craw et al ., ; Wang et al ., ; Liu et al ., ). One interpretation may be that sulphide ores were derived from the magmatic sources and the sulphide isotopic fractionation took place in process of the Au deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The sulphide ores have δ 34 S values of −23.2‰ to −0.5‰ (average −10.6‰) showing a wide negative range. This feature is similar as some sediment‐hosted orogenic gold deposits distributed in the northern margin of the NCC, in the eastern part of the Yilgarn Craton or in New Zealand (Craw et al ., ; Wang et al ., ; Liu et al ., ). One interpretation may be that sulphide ores were derived from the magmatic sources and the sulphide isotopic fractionation took place in process of the Au deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic types of some of these gold deposits are still controversial. Based on the disseminated style of mineralization, alteration, the submicroscopic state of gold and the geochemical association of the Au‐As‐Hg‐Sb, some deposits were classified as the Carlin‐type gold deposit (Liu et al, 2014; Peng et al, 2018) or the Carlin‐like gold deposit (Liu et al, 2018; Liu et al, 2019; Liu, Dai, et al, 2015; Liu, Liu, et al, 2015). However, in view of their relationships to faults and shear zones and to the enrichment of CO 2 , many gold deposits were recognized as orogenic gold deposits (Li et al, 2018; Liu et al, 2016; Sui et al, 2018; Yang et al, 2016; Yu, Qiu, Nassif, et al, 2020; Yu, Qiu, Sai, et al, 2020; Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Northeast China is situated between two major Precambrian cratons in Northeast Asia: the Siberian Craton in the north and the North China Craton in the south (Figure ). Traditionally, northeast China was thought to be influenced by the Paleo‐Asian and Paleo‐Pacific tectonic domains during the Palaeozoic and Mesozoic, and this region has been intensively studied (e.g., Cao, Xu, Pei, & Zhang, ; Feng et al, ; Feng et al, ; Ge et al, ; Ge et al, ; Ge, Wu, Zhou, & Abdel Rahman, ; Han et al, ; Han et al, ; Han et al, ; Hu et al, ; Jahn, Wu, & Chen, ; Li et al, ; Liu, Wu, Qiu, & Li, ; Pei et al, ; Wilde, Wu, & Zhang, ; Wu et al, ; Wu et al, ; Wu, Sun, Jahn, & Wilde, ; Wu, Sun, Li, Jahn, & Wilde, ; Yang, Ge, Zhao, Dong, et al, ; Yang, Sun, Gou, & Hou, ; Yu, Wang, Xu, Gao, & Tang, ; Zeng, Guo, Zhou, & Duan, ; Zhang & Li, ; Zhang et al, ; Zhang et al, ). Recently, detailed geochronological and geochemical work in the northern part of northeast China has shown that, in addition to the strong influence of the Paleo‐Asian and Paleo‐Pacific tectonic domains, the region was also influenced to some extent by the Mongol–Okhotsk tectonic domain (e.g., Meng et al, ; Tang et al, ; Tang, Xu, Wang, Zhao, & Li, ; Tang, Xu, Wang, Zhao, & Wang, ; Wang, Xu, Wang, & Meng, ; Xu, Xu, Meng, & Wang, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%